Evaluation of bone with quantitative ultrasound in healthy Turkish children - Tüzün, Sansin; Karacan, Ilhan; Akarirmak, Ulkü; Kasapçopur, Ozgür; Arisoy, Nil (The Turkish Journal of Pediatrics, 2003)
In this study bone status was assessed using a quantitative ultrasound (QUS) technique at the calcaneus in 141 healthy, prepubertal, Turkish schoolchildren (80 girls, 61 boys) aged 6-12 years. Broadband ultrasound attenuation (BUA, DB/MHz) was measured with a prototype pediatric contact bone analyzer (CUBA, McCue Ultrasonics Ltd). The relation of age, body weight and height to BUA was assessed. BUA increased linearly with age in boys and girls (R=0.448, p=0.0001 and R=0.382, p=0.002, respectively). BUA values in boys tended to be higher than in girls, reaching significance only at the age of seven years with a 95% confidence interval. In conclusion, the measurement of BUA in the calcaneus with QUS has important clinical implications in assessing bone mass in children. Further studies in not only healthy children but also in those with metabolic bone diseases would be helpful in order to evaluate its sensitivity and reproducibility.